Is venture capital worth it? Effects on firm performance and founder returns - Florin, Juan (Journal of Business Venturing, 2005)
This paper extends research on venture capital (VC) finance by studying its effects on a venture's performance and on its founders' returns beyond an initial public offering (IPO). A “founder performance” construct, defined as a founder's financial and nonfinancial returns, is proposed and used to measure and compare returns to founders with returns to investors and firm performance. In general, venture characteristics pre-IPO and venture performance post-IPO were not significantly different when comparing ventures with and without VC backing. Only when VC backing is very high, do pre-IPO resources and funding improve significantly. However, higher levels of resource endowments did not seem to affect post-IPO performance for the venture or its investors. On the other hand, founders resorting to VC funding before taking their company public generated significantly less wealth for themselves and were less likely to remain as CEOs of their ventures after the IPO. Results suggest that founders motivated primarily by wealth creation and those motivated by remaining in control of their ventures should, in both instances, minimize VC backing when taking their ventures public. The finding that founder performance differs from venture and investor performance calls for future research to explore potential conflicts of interest that may arise from the double role of founders as principals and agents.